Tailoring interventions for impact: implementing evidence-based strategies for female genital schistosomiasis knowledge gaps in selected districts in Ghana - Tetteh, Comfort Dede; Ginindza, Themba G.; Ncayiyana, Jabulani R.; Manyeh, Alfred Kwesi (Frontiers in Tropical Diseases, 2025)
BackgroundAddressing the knowledge gaps for female genital schistosomiasis (FGS) among healthcare professionals and community members in endemic areas to improve early detection and management is crucial. In Ghana, limited knowledge, entrenched socio-cultural beliefs, and inadequate healthcare resources hinder effective FGS management. This study utilized a systematic intervention mapping (IM) approach to design targeted health promotion interventions in Ghana’s Lower Manya-Krobo and Shai Osudoku Municipalities.MethodsThe five IM steps are as follows:1) Conducting needs assessment and identifying implementation adopters; 2) developing program objectives and outlining the desired outcome and performance objectives; 3) selecting theoretical methods and designing implementation strategies; 4) developing implementation materials, and tools, and protocols; and 5) evaluate implementation outcome. During the needs assessment, surveys and focused group discussions with 856 women and 252 healthcare workers and discussions with community members highlighted widespread misinformation and gaps in knowledge, attitudes, and practices related to FGS. Stakeholders’ engagement then guided the mapping of context-specific interventions and the development of program objectives. Intervention materials, including FGS posters, jingles in four languages, screening tools, and reporting forms, were created and distributed through accessible local channels. Training sessions were also conducted to build healthcare workers’ diagnostic and management capacities.ResultsThe study revealed that Implementation mapping (IM), grounded in needs assessment and stakeholder involvement, facilitated the creation of tailored, evidence-based strategies. These strategies reached the intended population and improved awareness and attitudes among healthcare workers and community members. The findings emphasized the need for adaptive intervention that accounts for varying healthcare settings and community contexts to effectively address FGS knowledge gaps. It also revealed that the provision of adequate system support and needed logistics enhances FGS case diagnosis and management.ConclusionThe intervention in Lower Manya-Krobo Municipal enhanced public health outcomes by improving community awareness, case detection, and management of FGS, demonstrating its potential for broader application in endemic regions. The study highlighted the need for tailored approaches to address varying healthcare dynamics and resource constraints. Continued monitoring and evaluation are crucial to ensure the long-term sustainability and effectiveness of such interventions, offering valuable insights for policymakers, clinicians, and public health practitioners.